Pengembangan Instrumen Three-Tier Test Diagnostik pada Materi Sistem Koordinasi untuk Mengidentifikasi Miskonsepsi Peserta Didik di SMAN 2 Sinjai - Ariya, A. Aida; Muis, Abd.; Ismail, Ismail (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2025)
The aim of this study was to develop a diagnostic test instrument and to identify the level of misconceptions held by students regarding the topic of the coordination system. The development design of this research involved trials with Grade XI students at SMAN 12 Sinjai and field testing with Grade XI students at SMAN 2 Sinjai. The methods employed included test item development, interviews, and documentation. The resulting instruments consisted of test blueprints, test items, and answer keys. The test items underwent expert validation and were subjected to reliability testing, difficulty level analysis, and item discrimination index evaluation through all trial stages (one-to-one, small group, and field testing). Out of 30 test items that were validated, only 21 advanced to the final stage, namely the field test. The findings revealed that, on average, 40.47% of the 50 students experienced misconceptions, which were categorized into two main indicators. The highest misconception rates in the coordination system topic were found in the indicators related to the structure of the central and peripheral nervous systems, as well as the structure and function of sensory organs, with an average misconception rate of 56% for the relevant test items. Based on the results of developing the three-tier diagnostic test on the coordination system material, it can be concluded that the instrument is effective and appropriate for identifying students' misconceptions on the topic.